ANALISIS PENGARUH LIQUIDITY, LEVERAGE DAN ACTIVITY TERHADAP PROFITABILITY KOPERASI DI KABUPATEN TOLITOLI - Mardiana, Mardiana (Katalogis, 2015)
The objective of this research is to explore and analyze simultaneous and partial effects of liquidity, leverage, and activity on profitability in cooperatives in Tolitoli Regency in 2011-2012. The sample is selected based on purposive sampling technique. The samples include cooperatives that still exist, performed RAT in 2011-2012 fiscal year, and have positive net income. Based on these criteria, the research selects 20 cooperatives out of 120 cooperatives as its samples. Technique of analysis is multiple linear regressions. The data is processed with statistical product program and service solution (SPSS 16.0) and classical assumption test. This research also runs hypothesis test with the F-statistic to test simultaneous effect of regression coefficients. In addition, it performs t-test to examine the partial effect of regression coefficient with a significance level of 5%. The results show that : 1) liquidity, leverage, and activity simultaneously have significant effects on profitability of cooperatives in Tolitoli of 0,004; 2) liquidity partially affects profitability of cooperatives in Tolitoli of 0,047; 3) leverage insignificantly (negative)has partial effects on profitability of cooperatives in Tolitoli of 0,296; 4) activity partially have significant effects on profitability of cooperatives in Tolitoli of 0,021.